The relationship between addiction severity and codependency level in individuals with substance use disorder - Akay, Osman; Albal, Esra; Güleşen, Gülten; Umut, Gökhan (Journal of Dependence, 2025)
Objective: This study aimed to examine the relationship between the addiction severity of individuals diagnosed with substance use disorder and the spouse addiction levels of family members. Method: Data were collected from 146 individuals and 146 family members who received addiction treatment at the adult detoxification center of a mental health hospital in Istanbul. Data were collected using sociodemographic information forms, the Addiction Profile Index (API), and the Codependency in Addiction Assessment Form (CAAF). Results: Of the 146 study participants, 128 (87.7%) were male; 84 of them (57.5%) were between the ages of 26 and 45 years. A total of 86 (58.9%) were primary school graduates and 70 (47.9%) were married. The average score of the male participants on API (X = 6.87) was higher than the average score of the female participants (X = 5.91). Of the relatives, 96 (65%) were women, 42 (28.8%) were mothers, and 71 (48.6%) were between the ages of 45 and 65 years. It was observed that whether the participants had low, medium, or high addiction severity did not make a difference in the scores they received from the CAAF scale. Conclusion: Women, those with children, those with chronic illnesses, those with a primary school education, those who were divorced, and those aged 45–65 had higher levels of codependence. These data show that families also need support when working with people with alcohol- or substance-use disorder.